Factors influencing Lyme borreliosis risk perception in Europe: a cross-sectional multi-country survey study - Emily Colby; L. Hannah Gould; Ye Tan; Andreas Pilz; Gordon Brestrich; Jennifer C. Moisi; James H. Stark (BMC Public Health)
Abstract Background Lyme borreliosis (LB) is the most common vector-borne disease in Europe. Research on factors that shape LB risk perception in Europe is limited. This study explores the potential drivers of LB risk perception in the general adult (18–65 years) population of twenty European countries, such as urbanicity, socioeconomic status, dog ownership, gender, age, and tick and LB diagnosis history. Methods Data were obtained from a 2022 survey of 28,034 adults aged 18–65 years in twenty European countries. The survey included questions on knowledge, attitudes, and practices related to ticks and LB. Respondents were categorized into three income levels (low, middle, or high) based on country-specific income tertiles. Descriptive statistics were calculated, and differences in responses to survey items by income level were assessed using chi-square tests. Risk perception was measured from a survey question asking respondents to rate their risk of contracting LB on a five-point scale from “very low risk” to “very high risk.” Ordinal logistic regression modeled the relationship between predictor variables and LB risk perception. Results Having a past LB diagnosis (adjusted odds ratio [AOR]: 3.96, 95% confidence interval [CI]: 3.38–4.64) was most strongly tied to increased LB risk perception. Knowing someone with a past LB diagnosis or having a past tick bite, were also significantly associated with higher risk perception (AOR: 2.11, 95% CI: 1.97–2.27, and AOR: 1.71, 95% CI: 1.60–1.84, respectively). High-income respondents were most likely to report a past tick bite (55.4%, 95% CI: 53.5–57.3%) and a past LB diagnosis (13.5%, 95% CI: 12.1–14.8%). Conclusions Experience with ticks and LB (i.e., via bites or diagnoses) may play a key role in shaping LB risk perception among European adults. Dog ownership and demographic factors such as gender and age may also influence LB risk perception. These results could help LB educational campaigns addressing knowledge and perception gaps.